(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: The purpose of this study is to find propotion of fractured orbital walls in the maxillofacial trauma cases and its associated maxillofacial fracture treated in the Oral Maxillofacial Clinic Oral Maxillofacial ward and operation theatre of Hospital USM in Kelantan, Malaysia. Materials and methods: From July 2013 to June 2018, records of patients who sustained maxillofacial fractures and presented them to the Accident and Emergency Department, Oral Maxillofacial Clinic, Hospital USM were reviewed, recorded, and analyzed. There are 294 patients whose data has been collected because they met the inclusion criteria. Each patient with a complete medical record was reviewed. Data were collected under the variables: Zygomatic Complex, Zygomatic Arch, Nasal, Maxillary Sinus, Le Fort I, Le Fort II, Le Fort III, Orbital Wall, Alveolar Process, Symphysis of Mandible, Condyle of Mandible, Ramus of Mandible, Maxillary Bone and Mandibular Bone of maxillofacial fracture. The fractured orbital walls in these cases was reviewed. At the first stage, all the selected variables will be screened for their important clinical point of view. The SPSS software version 26.0 was used to determine all possible factors contributing to orbital wall fracture. Results: This was a retrospective cross-sectional analysis of the medical records of 294 patients with maxillofacial fracture treated in the Oral Maxillofacial Clinic and Oral Maxillofacial ward, Hospital USM. There were 228 (77.3%) men and 66 (22.4%) women included in this study. The most common age range is 11-20 years (39.8%), 21-30 years (26.2%). Maxillary Bone Fracture (0.371; p <0.05), Maxillary Sinus Fracture (0.180; p <0.05), Zygomatic Arch Fracture (0.127; p <0.05) were found to be the most affected site, which had a positive correlation with an orbital fracture of the maxillofacial trauma cases. A path analysis based on the Spearman correlation was developed by taking into account significant correlations at the level of 0.05. Conclusion: Using the matrix spearman correlation, multiple response analysis (MRA), path analysis, we discovered a clear connection between orbital wall fracture and several other factors. This discovery will aid in the understanding of the most common fracture and the causes of orbital wall fracture in maxillofacial trauma. The Zygomatic Arch Fracture, Maxillary Sinus Fracture, and Maxillary Bone Fracture were found to have a significant relationship with the orbital wall when the significance level was set at 0.05. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 744-750